2007
DOI: 10.1111/j.1365-246x.2007.03405.x
|View full text |Cite
|
Sign up to set email alerts
|

Whole mantle SH velocity model constrained by waveform inversion based on three-dimensional Born kernels

Abstract: SUMMARY A whole mantle SH velocity model is obtained by using a unique data set and techniques. Body and surface waveforms including major and multi‐orbit phases are used as a data set and are inverted by using 3‐D Born kernels. The resultant model, SH18CE, reveals the different natures of the two major upwelling systems: the strong low velocity anomalies beneath Africa extend for more than 1000 km from the core–mantle boundary (CMB), whereas those beneath the Pacific are restricted to 300–400 km from the CMB.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 39 publications
1
48
0
Order By: Relevance
“…The low-velocity conduits ascend from broad low-velocity anomalies immediately above the CMB. Takeuchi (2007Takeuchi ( , 2009) obtained a similar image of the S-velocity structure from the waveform inversion of long-period transverse records (slower by 1.5-2%). On the other hand, some tomographic studies showed a large (700-1000 km in diameter), dome-like low-S-velocity anomaly (slower by 1.5-2%), occurring only in the lowermost mantle (Masters et al, 2000;Ritsema and van Heijst, 2000) or extending from the CMB to the middle-lower mantle (Figs.…”
Section: Seismic Images Obtained From the Global Datamentioning
confidence: 87%
“…The low-velocity conduits ascend from broad low-velocity anomalies immediately above the CMB. Takeuchi (2007Takeuchi ( , 2009) obtained a similar image of the S-velocity structure from the waveform inversion of long-period transverse records (slower by 1.5-2%). On the other hand, some tomographic studies showed a large (700-1000 km in diameter), dome-like low-S-velocity anomaly (slower by 1.5-2%), occurring only in the lowermost mantle (Masters et al, 2000;Ritsema and van Heijst, 2000) or extending from the CMB to the middle-lower mantle (Figs.…”
Section: Seismic Images Obtained From the Global Datamentioning
confidence: 87%
“…The regions are thus considered to have lower-density anomalies; this is also opposite of what would be expected from thermal anomalies. (Takeuchi, 2007), SAW24B16 (Mégnin and Romanowicz, 2000), SB4L18 (Masters et al, 2000), S20RTS (Ritsema et al, 1999), and S362D1 (Gu et al, 2001). The distance and direction from the center of the figure show the radius and the longitude of the central points, respectively.…”
Section: Possibly Detectable Chemical Heterogeneitiesmentioning
confidence: 99%
“…I consider here the following 3D density model: (1) the low-velocity region beneath Africa has +10% density anomalies, (2) the region beneath East Antarctica has −10% density anomalies, and (Takeuchi, 2007), SAW24B16 (Mégnin and Romanowicz, 2000), SB4L18 (Masters et al, 2000), S20RTS (Ritsema et al, 1999), and S362D1 (Gu et al, 2001). The average of these five sections (labeled as AVERAGE) is also plotted.…”
Section: Detectability Of the Focused Featuresmentioning
confidence: 99%
See 2 more Smart Citations